Kinerja Birokrasi Penghapusan Barang Inventaris Lainnya pada Bidang Aset Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Utara - Suaidi Harahap; Yusniar Lubis; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to evaluate the performance of the inventory removal bureaucracy at BPKAD Provsu by considering public performance concepts such as Relevance, Efficiency, Effectiveness, Utility, and Sustainability. The research method used is qualitative with data collection procedures in the form of observation, interviews, and documentation. Data analysis technique used the Miles, Huberman, and Saldana data analysis model. The results showed that the bureaucracy's performance in the administration of regular hajj pilgrimage transfers in the Financial and Regional Asset Management Agency of North Sumatra Province has met the service standards according to the performance theory by Pollit & Bouckaert. However, to improve the performance of the inventory removal bureaucracy, new innovations and SOPs are needed for the difficult-to-find inventory removal processes. These findings can be used as a basis for developing strategies and policies to improve bureaucracy performance in inventory removal in the future.